100 cupboards - Wilson, Nathan D. (100 cupboards, 2007)
After his parents are kidnapped, timid twelve-year-old Henry York leaves his sheltered Boston life and moves to small-town Kansas, where he and his cousin Henrietta discover and explore hidden doors in his attic room that seem to open onto other worlds.